Heat transfer enhancement in a flat plate solar collector with different flow path shapes using nanofluid. (February 2020) - Saffarian, Mohammad Reza; Moravej, Mojtaba; Doranehgard, Mohammad Hossein
Abstract: In the present study, in addition to using nanofluid, the flow direction in a flat plate solar collector is changed to increase the convective heat transfer coefficient. To this end, U-shaped, wavy and spiral pipes with identical pipe lengths on a flat plate collector are simulated. Three-dimensional and steady state equations of continuity, momentum, SST k - ω turbulence model, and energy are solved. Al2 O3 /water and CuO/water nanofluids are used in volume fractions of 1% and 4%. Results show that using wavy and spiral pipes can significantly increase the heat transfer coefficient and Nusselt number. Also, it is observed that the pressure drop has its highest value for the wavy pipes. In all cases, the heat transfer coefficient increases by using nanofluid instead of water. In all cases except for the CuO 4%, the Nusselt number has decreased due to a remarkable increase in thermal conductivity by adding nanoparticles to water. Results reveal that by using wavy pipes and CuO/water nanofluid with a volume fraction of 4%, the heat transfer coefficient can increase up to 78.25%. Highlights: Flow direction in pipes of a collector is changed to increase heat transfer coefficient. U-shaped, wavy and spiral pipes with identical lengths used on a flat plate collector. Al2 O3 /water and CuO/water nanofluids are used with volume fractions of 1% and 4%. Results show that using wavy pipe and CuO/water, heat transfer increases by 78.25%.